A Cause, but no Rebels? - Anne Waldrop; Stein Sundstøl Eriksen (Journal of Extreme Anthropology)
This article analyzes the political activities of residents in a 50-year-old slum in New Delhi. Based on long-term fieldwork undertaken periodically between 2004 and 2019, we describe the forms of oppression experienced by slum residents, how they cope in their everyday lives and how they have responded to their oppression. In order to understand the nature of slum residents’ political activity, we also analyze forms of group consciousness and solidarity among residents. We identify three main channels through which slum residents act politically: by voting, by taking part in protests and demonstrations, and by using informal intermediaries. We show that they are fully aware of being oppressed and express dissatisfaction with the government and ‘the rich’. However, their political activities are quite limited and constrained by the structural context within which they act. Their primary goal is to be included on equal terms in the existing system, not to change that system. Hence, their strategies can be described as affirmative rather than transformative. The analysis brings out three main points: First, that without external assistance slum residents lack the organizational capacity for sustained political mobilization; second, therefore their main way to seek political influence is through local intermediaries; and third, that while their reliance on intermediaries enables them to access certain goods and services it also paradoxically reinforces their marginalization.